Tendering and estimating strategies In contractor organization - Liana Syafawati, Mohamad Azmi (2017)
The contractors’ survival in the construction industry depends on number of projects they operate. If the contractors fail to secure and win the project, the company will not be able to survive in a long time. But to remain survived, the contractors have to compete to other registered contractors. The competitions among them are stiff. Therefore, this study is carried out to identify factors to improve tendering and estimating efficiency also to propose a sustainable method to win bid in tendering. The study involved the G7 contractors registered with CIDB that have been involved in project related to Public Work Department (PWD) tender in area of Kuala Lumpur. The total of 120 questionnaires was distributed and only 103 were returned answered which give a value of 86%. From the study, the factors to improve the tendering and estimating efficiency are skill and experience of estimator, and skill and experience of the purchasers and evaluate previous bidding performance, evaluation on previous bidding performance, monitoring on submitting tender and size of the project. For the factors to propose a sustainable method to win bid in tendering are contractors own plants or subsidiary companies, maintain a lower and effective opening cost, and minimize overhead cost by maintain on the required numbers, quality of staff needed.